PENGARUH PENERAPAN E-GOVERNMENT ABSENSI ELEKTRONIK BERBASIS BIOMETRIK TERHADAP DISIPLIN KERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISDUKCAPIL) KOTA BUKITTINGGI - Andanu, Willy Novri; Putri , Sinta Westika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Work discipline is very important aspect in order to improve the quality of public services and the performance of government organizations. However, employee discipline problems such as tardiness and absence without explanation are still found in various government agencies, including at the Population and Civil Registration Office (Disdukcapil) of Bukittinggi City. One of the efforts made to improve employee discipline is by the implementation of e-government in the form of biometric-based electronic attendance systems. This study aims to determine the effect of implementing biometric-based electronic attendance e-government on employee work discipline at the Population and Civil Registration Office (Disdukcapil) of Bukittinggi City. This study uses a quantitative approach with a simple linear regression method. Data collection techniques were carried out through questionnaires distributed to employees and supported by observation and documentation. The results showed that the implementation of biometric-based electronic attendance e-government had a positive and significant effect on employee work discipline. The biometric attendance system is able to increase attendance accuracy, transparency, and employee compliance with working hours regulations. These findings indicate that the implementation of digital technology in personnel administration can support the improvement of employee discipline and public service quality.